Prevalence and factors associated with gynoid lipodystrophy in Brazilian adolescent girls: a cross-sectional study - Soares, Juliana L. M.; Rocha, Vanessa A.; Sanudo, Adriana; Miot, Hélio Amante [UNESP]; Bagatin, Ediléia (Wiley, 2022)
Background: Gynoid lipodystrophy (GLD), or female cellulitis, is a chronic multifactorial disorder characterized by the irregular appearance of the skin surface on the thighs and gluteal regions, which affects 80–90% of women after puberty. No curative treatments are available, and there is a paucity of epidemiological studies related to its prevalence, quality of life impact, and risk factors. We aimed to identify the prevalence and factors associated with the development of GLD in Brazilian adolescent girls. Methods: A cross-sectional study examined adolescent girls from São Paulo, Brazil. The explored factors were grouped: familial history, gynecological and hormonal characteristics, exercise practice, nutrition and diet, anthropometric measures, body mass index, and body composition, according to GLD severity assessed through multivariate hierarchic statistics. Results: In total, 184 girls, aged from 12 to 18 years, were included in the study. The overall prevalence of GLD was 77.7% (CI 95% 71.7–82.1%); moderate and severe categories of GLD occurred in 56.5% (CI 95% 48.9–62.5%) of the sample. An impact on the quality of life was identified in 39.7% of the girls. GLD was independently associated with higher body mass index, early menarche, higher carbohydrate intake, lower water consumption, menstrual irregularity, familial report of GLD, and less exercise practice. Conclusion: Gynoid lipodystrophy is a multifactorial disorder; its onset in adolescent girls is associated with familial occurrence, body composition, diet habits, exercise, and hormonal factors. These results support further interventions for GLD prevention and treatment.